2015
DOI: 10.1371/journal.pone.0133372
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function in Homodimeric Enzymes: Simulations of Cooperative and Independent Functional Motions

Abstract: Large-scale conformational change is a common feature in the catalytic cycles of enzymes. Many enzymes function as homodimers with active sites that contain elements from both chains. Symmetric and anti-symmetric cooperative motions in homodimers can potentially lead to correlated active site opening and/or closure, likely to be important for ligand binding and release. Here, we examine such motions in two different domain-swapped homodimeric enzymes: the DcpS scavenger decapping enzyme and citrate synthase. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 51 publications
6
31
0
Order By: Relevance
“…We focus on the lowest frequency nontrivial modes of motion, which represent large‐scale motions that are likely to be on relatively long (ms) timescales. Recent studies have shown excellent agreement between flexible motion simulations and large‐scale functional motion in enzymes, with results from the calculations found to be consistent with those produced by molecular dynamic simulations . Example results are shown in Fig.…”
Section: Resultssupporting
confidence: 74%
“…We focus on the lowest frequency nontrivial modes of motion, which represent large‐scale motions that are likely to be on relatively long (ms) timescales. Recent studies have shown excellent agreement between flexible motion simulations and large‐scale functional motion in enzymes, with results from the calculations found to be consistent with those produced by molecular dynamic simulations . Example results are shown in Fig.…”
Section: Resultssupporting
confidence: 74%
“…We use a recent protein flexibility modeling approach, combining methods for deconstructing a protein structure into a network of rigid and flexible units (First) with a method that explores the elastic modes of motion of this network, and a geometric modeling of flexible motion (Froda) . The usefulness of this approach has recently been shown in a variety of systems (see the starting sections of Supporting Information for more details.). Methods similar in spirit, exploring flexible motion using geometric simulations biased along “easy” directions, have also been implemented using Frodan and NMSim .…”
Section: Methodsmentioning
confidence: 99%
“…The oligomeric organization of enzymes plays an important role in numerous biological processes, such as allosteric regulation and thermal stability. Moreover, the active site of an enzyme is frequently formed at the subunit interface, which places enzymatic activity under the regulation of oligomerization . The importance of protein oligomerization can be studied by comparing the catalytic properties of the monomeric and oligomeric enzyme forms.…”
Section: Discussionmentioning
confidence: 99%